Improving Indonesia's Culinary Image Through Gastrodiplomacy at the MSMEs Restu Mande - Astuty, Nadhira Triana; Setiawati, Sri Dewi (Komunikator, 2025)
As part of gastrodiplomacy, Micro, Small, and Medium Enterprises (MSMEs) play an important role in introducing Indonesian culinary products to the global market. However, they continue to face challenges, particularly in the transition to digital platforms. This study analyzes the strategies implemented by MSMEs in building the image of Indonesian cuisine—specifically rendang—and examines how digital content is used to shape perceptions in the international market. This research employs a qualitative approach using a case study of MSMEs Restu Mande. Data were collected through interviews, observations, and digital content analysis, and analyzed using the Miles, Huberman, and Saldaña technique with the support of Nvivo 12 Pro. The study utilizes the Associative Network Memory Model and Brand Awareness theory. The findings show that Restu Mande builds a positive international image of rendang through storytelling and digital content. Collaboration with local communities and participation in culinary festivals contribute to strengthening brand awareness as a collection of associative nodes that position rendang as an authentic symbol of Indonesian cuisine. The narratives presented by Restu Mande emphasize community empowerment, collaboration, and the spirit of gotong royong, reflecting distinctive aspects of Indonesian culture